2022
DOI: 10.3390/foods11182864
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Preliminary Application of a Novel Lipoxygenase from Enterovibrio norvegicus

Abstract: Lipoxygenases have proven to be a potential biocatalyst for various industrial applications. However, low catalytic activity, low thermostability, and narrow range of pH stability largely limit its application. Here, a lipoxygenase (LOX) gene from Enterovibrio norvegicus DSM 15893 (EnLOX) was cloned and expressed in Escherichia coli BL21 (DE3). EnLOX showed the catalytic activity of 40.34 U mg−1 at 50 °C, pH 8.0. Notably, the enzyme showed superior thermostability, and wide pH range stability. EnLOX remained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 59 publications
5
14
0
Order By: Relevance
“…Aanangi et al study on mung beans showed higher LOX activity between the pH ranges of 6.0–7.0. Similar effects were observed in the Zhang et al study, where the LOX relative activity increased linearly from ∼0 to around 100% with a pH increase from 3.5 to 8.0, respectively. However, in the current study, an initial decline in LOX activity was observed, possibly due to the denaturation of a small portion of LOX by plasma reactive species.…”
Section: Results and Discussionsupporting
confidence: 88%
“…Aanangi et al study on mung beans showed higher LOX activity between the pH ranges of 6.0–7.0. Similar effects were observed in the Zhang et al study, where the LOX relative activity increased linearly from ∼0 to around 100% with a pH increase from 3.5 to 8.0, respectively. However, in the current study, an initial decline in LOX activity was observed, possibly due to the denaturation of a small portion of LOX by plasma reactive species.…”
Section: Results and Discussionsupporting
confidence: 88%
“…10 Enzymes with combination properties of activity in a mild temperature, superior thermal stability, good substrate specificity, and high enzyme activity are required for industrial applications. 50 Therefore, it is necessary to make molecular modifications to enzymes with existing properties. A rational design is often applied to predict important amino acid residue sites in order to improve the efficiency and feasibility of protein engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mining of thermophilic and mesophilic enzymes with good thermostability solved the problem of short half-lives, the inactivity of thermophilic enzymes at mild temperatures and the low activity or poor substrate specificity of mesophilic enzymes that have good thermostability limited their industrial applications . Enzymes with combination properties of activity in a mild temperature, superior thermal stability, good substrate specificity, and high enzyme activity are required for industrial applications . Therefore, it is necessary to make molecular modifications to enzymes with existing properties.…”
Section: Discussionmentioning
confidence: 99%
“…The data for all bacteria included in this statistical analysis are provided in Table S3. The bar at the right shows total binding site bottom volumes of experimentally characterized LOXs [147,[149][150][151][152][153][154] along with their activities. "Human-related" and "plant-related" groups correspond (ω-6)-LOX activity while "marine-related" group is shifted towards (ω-12)-LOX activity.…”
Section: Vertebrate" Samples)mentioning
confidence: 99%
“…Compared with the binding site bottom volumes of experimentally characterized LOXs [147,[149][150][151][152][153][154] (calculated by the same method), the "human-related" and "plant-related" LOX groups appear to correspond to (ω-6)-LOXs. The Pseudomonas aeruginosa and Burkholderia thailandensis LOXs (both belonging to the "human/vertebrate" group in our statistics) have total binding site bottom volumes (472.2×10 -3 nm 3 and 475×10 -3 nm 3 , respectively) near to the mean of the "human-related" group.…”
Section: Vertebrate" Samples)mentioning
confidence: 99%